(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: The pyramid of evidence is usually cited when discussing evidence-based medicine or dentistry (EBM/EBD), with randomised controlled(efficacy) trials and their syntheses (in the form of systematic reviews and meta-analyses) being the strongest category of evidence. Thus, confounding bias is potentially avoided, similar to a randomised controlled experiment. Aim’s & Objectives: Clinical research should be a significant factor in dentists’ decisions on dental materials. Design, execution, analysis, and reporting of studies have an effect on their usefulness. We evaluate issues with current studies and highlight potential areas for improvement. Methods & Materials: On the basis of systematically and non-systematically gathered data, we illustrate where and why present clinical dentistry studies produce suboptimal outcomes. Taking cues from the field of general health, we propose future directions for clinical dental material research. Results: Randomized controlled (efficacy) trials continue to be a cornerstone of dental material science because they eliminate selection bias and, if well-designed and done, offer excellent internal validity. In light of their expense and low external validity, alternatives such as practice-based or pragmatic controlled trials or observational research might supplement the existing body of knowledge. Prior to implementation, researchers should focus on study comparators and setting (answering questions pertinent to clinical dentistry) and pay close attention to statistical power, taking into account the study objective (superiority or non-inferiority trial), the anticipated event rate, and attrition. In the absence of a core result set, patients and other stakeholders should be consulted in the selection of study outcomes. Studies ought to be pre-registered, and reporting must follow to guidelines. Statistical analysis should account for potential clustering. Significance: Numerous clinical research in dental material science are underpowered, with little validity and practical use for making daily decisions. In order to improve dental treatment, dental researchers should replicate efforts in other medical professions to make clinical trials more valid and useful.